IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISME UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA SISWA SEKOLAH DASAR - Novita Sari Hasibuan; Joko Sutarto (STKIP Subang, 2025)
Effective learning requires an approach that aligns with how students construct knowledge. Constructivist learning theory emphasizes that students actively construct their own understanding through meaningful learning experiences. This article discusses the application of constructivist theory in the learning process in elementary schools, specifically in improving understanding of academic concepts. With this approach, teachers are no longer the sole source of information, but rather act as facilitators, encouraging exploration, discussion, and reflection. Constructivist-based learning has also been shown to help students connect new knowledge with prior experiences, making learning more personal and in-depth. Through this study, it is hoped that teachers can design more participatory and contextual learning strategies to optimally support children's cognitive development.